The Running Tongue: Collaboration, Choice and Community - Davies, Siobhan; Hinton, David; Ellis, Simon (The International Journal of Screendance, 2015)
The Running Tongue is a new film installation work by Siobhan Davies and David Hinton. It features a woman—Helka Kaski—running continuously and then appearing or jump-cutting into different and very brief scenes—or "visions"—that have been developed with Davies and Hinton by more than 20 independent dance artists in the UK. Such a large-scale collaboration resulted in a complex series of negotiations between the artists. In this interview, Davies and Hinton discuss The Running Tongue with IJSD co-editor—and one of the artists involved in the project—Simon Ellis.